Accuracy Improvement of Breast Tumor Detection based on Dimension Reduction in the Spatial and Edge Features and Edge Structure in the Image - Samaneh Sadat Seyed Abolghasemi; Mehran Emadi; Mohsen Karimi (Majlesi Journal of Electrical Engineering, 2024)
Ultrasound images and ultrasound imaging method is an effective method in examining the challenges, problems and diseases related to the breast in women. The contrast of these images is generally very weak, however, the tumor tissue and calcium grains are evident in it. Methods based on image processing are widely used in breast tumor diagnosis and classification. In this article, a method based on pattern recognition is presented in order to detect the type of tumor. GLCM-based features are extracted from the target area, and Gabor and texture features. Then it is reduced with the help of dimension reduction methods based on principal component analysis. Finally, with the help of the improved classification of Ada KKN with ELM, they are grouped into three categories. Evaluation criteria such as Accuracy (98.81%),  sensitivity (91.51%) and specificity (94.54%) compared to other similar methods show the superiority of the proposed method.